Investigation of α‐glucosidase inhibitory metabolites from Tetracera scandens leaves by GC–MS metabolite profiling and docking studies - Ahmed, Nokhala; Siddiqui, Mohammad Jamshed Ahmad; Ahmed, Qamar Uddin; Ahamad Bustamam, Muhammad Safwan; Zakaria, Zainul Amiruddin (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Abstract:  Stone  leaf  (Tetracera  scandens)  is  a  Southeast  Asian  medicinal  plant  that  has  been  traditionally used  for  the  management  of  diabetes  mellitus.  The  underlying  mechanisms  of  the  antidiabetic  activity have  not  been  fully  explored  yet.  Hence,  this  study  aimed  to  evaluate  the  α‐glucosidase  inhibitory potential  of  the  hydromethanolic  extracts  of  T.  scandens  leaves  and  to  characterize  the  metabolites responsible  for  such  activity  through  gas  chromatography–mass  spectrometry  (GC–MS)  metabolomics. Crude  hydromethanolic  extracts  of  different  strengths  were  prepared  and  in  vitro  assayed  for  αglucosidase  inhibition.  GC–MS analysis was  further  carried out and the  mass spectral data  were correlated to  the  corresponding  α‐glucosidase  inhibitory  IC50  values  via  an  orthogonal  partial  least  squares  (OPLS) model.  The  100%,  80%,  60%  and  40%  methanol  extracts  displayed  potent  α‐glucosidase  inhibitory potentials.  Moreover,  the  established  model  identified  16  metabolites  to  be  responsible  for  the  αglucosidase  inhibitory  activity  of  T.  scandens.  The  putative  α‐glucosidase  inhibitory  metabolites  showed moderate  to  high  affinities  (binding  energies  of  −5.9  to  −9.8  kcal/mol)  upon  docking  into  the  active  site  of Saccharomyces  cerevisiae  isomaltase.  To  sum  up,  an  OPLS  model  was  developed  as  a  rapid  method  to characterize  the  α‐glucosidase  inhibitory  metabolites  existing  in  the  hydromethanolic  extracts  of  T. scandens  leaves  based  on  GC–MS  metabolite  profiling.